Serum Albumin as a Prognostic Marker for Serious Non-AIDS Endpoints in the Strategic Timing of Antiretroviral Treatment (START) Study. (13th December 2017) - Ronit, Andreas; Sharma, Shweta; Baker, Jason V; Mngqibisa, Rosie; Delory, Tristan; Caldeira, Luis; Ndembi, Nicaise; Lundgren, Jens D; Phillips, Andrew N; ,
Abstract : Results from the Strategic Timing of Antiretroviral Treatment (START) study showed that serum albumin is associated with serious non-AIDS occurrence in HIV-infected persons with high CD4 cell counts. Abstract: Background: Serum albumin may be used to stratify human immunodeficiency virus (HIV)–infected persons with high CD4 count according to their risk of serious non-AIDS endpoints. Methods: Cox proportional hazards models were used to analyze the risk of serious non-AIDS events in the Strategic Timing of Antiretroviral Treatment (START) study (NCT00867048) with serum albumin as a fixed and time-updated predictor. Models with exclusion of events during initial follow-up years were built to assess the ability of serum albumin to predict beyond shorter periods of time. Secondarily, we considered hospitalizations and AIDS events. Results: Among 4576 participants, 71 developed a serious non-AIDS event, 788 were hospitalized, and 63 experienced an AIDS event. After adjusting for a range of variables associated with hypoalbuminemia, higher baseline serum albumin (per 1 g/dL) was associated with a decreased risk of serious non-AIDS events (hazard ratio, 0.37 [95% confidence interval, .20–.71]; P = .002). Similar results were obtained in a time-updated model, after controlling for interleukin 6, and after excluding initial follow-up years. Serum albumin was independently associated with hospitalization but not with risk of AIDS. Conclusions: A low serum albumin level is a predictor for short- and long-term serious non-AIDS events, and may be a useful marker of risk of noncommunicable diseases, particularly in resource-limited settings.